Pathophysiological Significance And The Role Of Exogenous Hydrogen Sulfide (H2S) In A Combined State Of Hypertension And Diabetes And Its Effect On Renal Excretory And Haemodynamic Functions - Ahmad, Fiaz Ud Din (2012)
Hypertension and diabetes is a common co-morbidity that often coexists. Both diseases serve to induce and exacerbate each other. Hypertension and diabetes predispose the development of cardiovascular disease (CVD) and renal disease as their major complications. Coexistence of hypertension and diabetes results in rapid development of nephropathy. Endogenous H2S is recognized as a novel gaseous transmitter. Vascular tissues are capable of generating the measurable amounts of H2S with a concentration of ~46μM in the rat serum. H2S is involved in the regulation of blood pressure and also implicated in controlling the renal glomerular (vascular) and tubular functions. Present study was undertaken to test the hypothesis that exogenous H2S lowers the blood pressure and decreases the progression of nephropathy in hypertensive diabetic rats. SHR and DOCA-salt hypertension rat models were used in this study. DOCA-salt hypertension was produced from WKY rats. Diabetes was induced with a single injection of streptozotocin (STZ) at a dose of 40 mg/kg in freshly prepared ice cold sodium citrate buffer (0.1 mol/L, pH 4.5), intraperitoneally. One set of diabetic groups received NaHS, a H2S donor, at a dose of 56μmol/kg intraperitoneally in saline at the same time daily for 5 weeks. Blood pressure was measured in conscious rats and at the end of the treatment period in surgically prepared anesthetized rats. In addition, pulse wave velocity (PWV) and renal cortical blood perfusion were also observed. Metabolic data collection for renal function study was performed on days 0, 21 and 33 of a 35-day study. Plasma and urinary H2S levels, creatinine concentrations and electrolytes were measured on three different occasions throughout the 35-day period. Plasma and urinary H2S and creatinine concentrations were measured spectrophotometrically. Data, mean±SEM were analyzed using ANOVA and statistical significance was set at p < 0.05. Diabetic hypertensive groups of rats had higher blood pressure, low plasma and urinary H2S levels and renal dysfunction as evidenced by increased plasma creatinine, creatinine clearance and decreased urinary sodium to potassium ratio and renal cortical blood perfusion. In addition diabetic hypertensive rats had higher pulse wave velocity. Moreover diabetic rats exhibited increased creatinine clearance, plasma sodium, absolute sodium excretion and fractional sodium excretion. NaHS, a donor of exogenous H2S reduced the blood pressure and pulse wave velocity, increased the H2S levels in hypertensive diabetic rats and reversed the STZ-induced renal dysfunction. In addition, exogenously administered H2S decreased the plasma sodium and increased the creatinine clearance and absolute sodium excretion in treated rats. The findings of the present study suggest that exogenously administered hydrogen sulfide lowers the blood pressure and significantly reverses the STZ-induced increase in plasma creatinine, decrease in urinary sodium potassium ratio and reduced renal cortical blood perfusion, thereby conferring the protection against the progression of STZ-induced nephropathy in hypertensive rats.